Terbangan Menara as a Medium of Local Culture-Based Islamic Education in Kudus - Wahyu Mukti, Muhammad Panji; Sinaga, Syahrul Syah; Sugiarto, Eko (Program Studi Pendidikan Agama Islam, 2026)
Terbangan Menara Kudus is a traditional art form that combines music, Islamic poetry, and sacred performance conventions. This study aims to analyze the role of Terbangan Menara as a medium for Islamic education based on local culture. The research method used a descriptive qualitative approach with observation, interview, and documentation techniques, involving performers, managers, and the local community. The findings reveal that Terbangan Menara functions not only as a traditional musical performance but also as a medium for transmitting Islamic teachings, moral values, social solidarity, and cultural identity. The lyrics, rhythms, and collective performance practices reflect Islamic values such as togetherness, discipline, cooperation, and spirituality. Furthermore, Terbangan Menara demonstrates how Islamic education can be integrated with local wisdom without losing its religious essence. The study concludes that Terbangan Menara has significant potential as a model of local culture-based Islamic education that supports cultural preservation and strengthens community identity. Therefore, its preservation and development are important in promoting culturally rooted Islamic educational practices in Indonesia.